Advanced methodologies and technologies in system security, information privacy, and forensics - Khosrow-Pour, Mehdi, 1951- (IGI Global, 2019)
"This book presents emerging research and methods on preventing information breaches and further securing system networks. While highlighting the rising concerns in information privacy and system security, this book explores the cutting-edge methods combating digital risks and cyber threats"--